THE EPISTEMOLOGY OF USHUL FIQH AL-GHAZALI IN HIS BOOK AL-MUSTASHFA MIN USHUF FIQH نظرية المعرفة الأصولية عند الغزالي من خلال كتابه المستصفى من علم الأصول - Muhamad Subhi Apriantoro; Muthoifin Muthoifin (Profetika: Jurnal Studi Islam, 2021)
This study analyzed the epistemological theory of Ushul Fiqh, which is currently devoid of the interest of enthusiasts of the fundamentals of jurisprudence and followers of the philosophy of science. Given the demands to use this science cannot be separated from the development of his epistemology. For reference, this study evokes Al-Ghazali who has historically been a representative figure as a representative of classical thinkers. The data presented in this study are taken from the main source, Al-Mustasfa's book from the science of Ushul. This study concluded that Al-Ghazali's ushul fiqh epistemology is deductive rationality, very clearly reject non-rational arguments let alone metaphysics. Al-Ghazali has assumed that the senses can be used as a source of knowledge, Illustrated in three models of thinking, which are semantic thinking based on linguistic principles.Kajian ini menganalisis teori epistemologis ushul fikih, yang saat ini sepi dari minat peminat dasar-dasar fikih dan pengikut falsafah sains. Mengingat tuntutan untuk menggunakan ilmu ini tidak lepas dari perkembangan epistemologinya. Sebagai referensi, kajian ini membangkitkan Al-Ghazali yang secara historis merupakan sosok yang representatif sebagai wakil dari para pemikir klasik. Data yang disajikan dalam penelitian ini diambil dari sumber utama yaitu kitab Al-Mustasfa dari ilmu Ushul. Studi ini menyimpulkan bahwa epistemologi ushul fikih Al-Ghazali adalah rasionalitas deduktif, sangat jelas menolak argumentasi non-rasional apalagi metafisika. Al-Ghazali beranggapan bahwa indera dapat digunakan sebagai sumber ilmu, tergambar dalam tiga model pemikiran, yaitu berpikir semantik berdasarkan kaidah kebahasaan.